A simplified model for software inspection. Issue 12 (27th October 2014) - Misra, Sanjay; Fernández, Luis; Colomo‐Palacios, Ricardo
ABSTRACT Software inspection is considered a cost‐effective quality assurance technique in software process improvement. Although inspections detect the majority of defects in the early stages of the development process, this technique is not a common practice in the software industry, especially in small and medium enterprises. In this paper, we propose a model for the inspection process intended to be applicable and acceptable to both small and medium enterprises and large software organisations. The model was implemented in two organisations: one in a medium‐scale company and the other one in a department of a big company where its feasibility and benefits were confirmed. A comparison with recent alternative inspection models has also been performed showing the practicality of the proposal and ease of adoption and cost‐effectiveness. Copyright © 2014 John Wiley & Sons, Ltd.